Short-Term Outcomes of Intravitreal Faricimab Injection for Diabetic Macular Edema - Sentaro Kusuhara; Maya Kishimoto-Kishi; Wataru Matsumiya; Akiko Miki; Hisanori Imai; Makoto Nakamura (Medicina, 2023)
Background and Objectives: Faricimab is a novel bispecific antibody with Fab regions inhibiting both vascular endothelial growth factor-A and angiopoietin-2. Therefore, this study aimed to obtain short-term outcomes of intravitreal injection of faricimab (IVF) for the treatment of diabetic macular edema (DME) in daily clinical practice. Materials and Methods: A retrospective review was carried out on consecutive patients with DME who had been treated with IVF and were followed up for at least 1 month. Outcome measures included changes in logMAR best-corrected visual acuity (logMAR BCVA), central retinal thickness (CRT), number of IVF administrations, and safety. Clinical outcomes were also compared between the treatment-naïve and switch groups. Results: A total of 21 consecutive DME eyes from 19 patients were identified. The mean number of IVFs was 1.6 ± 0.8 during the mean follow-up time of 5.5 months. The overall mean logMAR BCVA following IVF was 0.236, 0.204, 0.190, and 0.224 at baseline, 1, 3, and 6 months, respectively, without a significant change from baseline to 1 month (p = 0.176) or for 6 months (p = 0.923). The overall mean CRT (μm) following IVF was 400.6, 346.6, 342.1, and 327.5 at baseline, 1, 3, and 6 months, respectively. CRT significantly decreased from baseline to 1 month (p = 0.001) but did not reach a significant level over 6 months following IVF (p = 0.070). No significant difference in BCVA or CRT was observed between the treatment-naïve and switch groups. No serious safety concerns were noted. Conclusions: IVF for the treatment of DME may preserve visual acuity and improve macular thickness without serious safety concerns in the short term in a real-world clinical setting.